1967
DOI: 10.1002/bit.260090409
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial phenomena governing adhesion of chlorella to glass surfaces

Abstract: SummaryInterfacial phenomena are direct,ly involved in the adhesion of a stJrain of Chlorella, a unicellular alga, to glass surfaces in simple ionic solutions. The principal mechanisms governing the adhesion appear to be electrostatic interaction between electrical dortble layers arid various specific surface interactions resulting from surface heterogeneity and ion adsorption. Under most conditions the algal cells and glass surfaces have negat,ive zeta potentials, and adhesion to gl will not occur; but if, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1974
1974
1996
1996

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…In other circumstances, the majority of the algae was removed by an average liquid velocity as low as 1.6 x 1 0 4m s-1. Hence, while fluid forces alone will not control microbial film, the evidence suggests that an appropriate selection or treatment of surface, control of ionic strength of the environment and a satisfactory fluid (Nordin et aL, 1967). References on curves relate to Table 6 velocity might result in a situation in which microorganisms will, or will not, adhere to the surface.…”
Section: F O R M a T I O N Of M I C R O B I A L Filmmentioning
confidence: 95%
See 4 more Smart Citations
“…In other circumstances, the majority of the algae was removed by an average liquid velocity as low as 1.6 x 1 0 4m s-1. Hence, while fluid forces alone will not control microbial film, the evidence suggests that an appropriate selection or treatment of surface, control of ionic strength of the environment and a satisfactory fluid (Nordin et aL, 1967). References on curves relate to Table 6 velocity might result in a situation in which microorganisms will, or will not, adhere to the surface.…”
Section: F O R M a T I O N Of M I C R O B I A L Filmmentioning
confidence: 95%
“…Such charges may be influenced by the conditions prevailing in the environment, for example, pH, electrolyte concentration and properties of the surface. These charges can set up considerable adhesive forces, as indicated by the results of Nordin et al (1967) shown in Fig. 5 where, given appropriate conditions, the Chlorella was not washed off the glass surface when the average liquid velocity through the test cell exceeded 3 m s-1.…”
Section: F O R M a T I O N Of M I C R O B I A L Filmmentioning
confidence: 97%
See 3 more Smart Citations